Adaptive fuzzy PID integrated renewable power management system for off grid and on grid conditions - Gopu, Veeranjaneyulu; Nagaraj, Mudakapla Shadaksharappa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Renewable source penetration into the distribution grid is merely a greater challenge as the powers from renewable sources are not stable and constant. Due to their sporadic operating states the power shared to the grid creates power quality issues. Therefore, an efficient adaptive PMA needs to be adopted for the control of these renewable sources, which controls the power extraction of these sources. For standard power sharing to the variable loads in the grid islanding state, the renewable sources are updated with the ESS module. In this paper, a low-rating distribution test system is considered connected with different renewable sources PV sources, wind farms, and fuel cell plants sharing renewable power. The PV source module is updated with AF-PID replacing the PI controller integrated PMA and ESS module for extensive control of the power of the generation unit during any operating condition. The DC and AC voltages are more stabilized by the upgraded PMA during grid islanding conditions. Mitigation of ripple and harmonic content is achieved by the AF-PID controller varying the proportional, integral, and derivative gains as per the error signal generated. A comparative analysis is carried out on the system validating the effectiveness of the AF-PID controller using MATLAB Simulink software.